The Effect of Applying Organizational Justice on Job Burnout (An Applied Study in the Municipality of Samawah) - Kadim, Jasim Rahi; Sabti, Yousif Mousa; Ali, Ghazanfar; Abbas, Yasir Abdullah; Shliot, adeq Mehdi (South Asian Journal of Social Sciences and Humanities, 2021)
The current research chose the dimensions of organizational justice (distributive justice, procedural justice, reactive justice) and the elimination of functional burnout (emotional stress, sagging feeling, and lack of a sense of achievement). The purpose of the research was to test whether organizational justice could contribute to reducing job burnout and standing at the level of both organizational justice, job burnout through the search for the problem through a group of questions centered on whether there is a correlation and influence between the research variables, and in light of this, a hypothetical model was built from which the main and sub-research hypotheses emerged. In order to test the validity of the hypotheses, data were collected through the questionnaire tool, which was prepared for this purpose, and the same was chosen for this purpose, represented by the size of 50 personnel working in (Samawah Municipality Directorate). The data were analyzed using a set of statistical methods and the results were extracted using the computer program SPSS. From their weak ability to influence, and the loss of meaningful action. Finally, the research presented a set of recommendations, which are necessary to reduce the state of job burnout felt by workers in the field of work, including the directorate’s management to take a new approach in strengthening organizational justice through fair treatment of workers, fairness in implementing administrative procedures and also on the directorate’s management to use methods modern management in reducing the state of separation of workers from their work by empowering workers, re-engineering human resources, redesigning the organizational structure, and promoting the introduction of technology in work.
Keywords: Organizational justice; Job burnout; Municipality of Samawah